The Dissolution of the Author in Literary Collaboration: Two Case Studies (Altre Modernità, 2018)
This essay considers the figure of the author within collaborative writing for fiction. My discussion draws on two case studies from the late nineteenth century, a historical moment when literary collaboration witnessed its efflorescence: the collaborative experiences of the Anglo-Irish Edith Somerville with Martin Ross, and of the American Brander Matthews with his various male collaborators. The author-figure promoted in both Somerville’s and Matthews’s metadiscourses challenges and subverts established post-Romantic notions of authorship, according to which the author is a solitary, hypertrophic genius. As a matter of fact, due to the sharing of textual spaces and the dispersal of authorial ownership and control implied in coauthorship, the collaborative author fades away into a diluted, deliberately weakened, blurred and elusive figure: a ghost that, according to coauthors themselves, is – and must remain – concealed behind the text. I therefore suggest that the collaborative trend of the late Victorian period produced an embryonic dismantling of the author – though not systematically theorised and today largely unknown of.
Keywords: coauthorship; literary collaboration; late Victorian literature; Brander Matthews; Somerville and Ross